Conocimiento, actitud, práctica e impacto legal frente a los eventos adversos en el servicio de odontología de la universidad Antonio Nariño sede Palmira. (2023)
Patient safety is a fundamental aspect of medical care that focuses on preventing errors and accidents in health care, and minimizing the risk of harm.